A Population-Specific Major Allele Reference Genome From The United Arab Emirates Population - Daw Elbait, Gihan; Henschel, Andreas; Tay, Guan K.; Al Safar, Habiba S. (Frontiers in Genetics, 2021)
The ethnic composition of the population of a country contributes to the uniqueness of each national DNA sequencing project and, ideally, individual reference genomes are required to reduce the confounding nature of ethnic bias. This work represents a representative Whole Genome Sequencing effort of an understudied population. Specifically, high coverage consensus sequences from 120 whole genomes and 33 whole exomes were used to construct population-specific major allele reference genome for the United Arab Emirates. When this was applied and compared to the archetype hg19 reference, assembly of local Emirati genomes was reduced by ~19% (i.e. some 1 million fewer calls). In compiling the United Arab Emirates Reference Genome (UAERG), sets of annotated 23,038,090 short (novel:1,790,171) and 137,713 structural (novel: 8,462) variants; their Allele Frequencies and distribution across the genome were identified. Population-specific genetic characteristics including loss-of-function variants, admixture, and ancestral haplogroup distribution were identified and reported here. We also detect a strong correlation between FST and admixture components in the UAE. This baseline study was conceived to establish a high-quality reference genome and a genetic variations resource to enable the development of regional population specific initiatives and thus inform the application of population studies and precision medicine in the UAE.